Моделі поширення радіосигналів міліметрового діапазону у мережах зв’язку 5G - Коляденко, Ю. Ю.; Чурсанов, М. О.; Водолажченко, О. В. (ХНУРЕ, 2021)
The scientific problem of determining the directions of increasing the efficiency of voice authentication systems is being solved. As the main direction, it is proposed to use the phase data of the voice signal, which is currently ignored. In this case, the main attention is paid to the procedures for preprocessing the registration materials and the linear prediction coefficients, which are calculated based on the phase data.
Keywords: моделі поширення радіосигналів; міліметрового діапазону